Twenty-five years of sport performance research in the Journal of Sports Sciences - Nevill, A.; Atkinson, G.; Hughes, M. (Journal of Sports Sciences, 2008)
In this historical review covering the past 25 years, we reflect on the content of manuscripts relevant to the Sport Performance section of the Journal of Sports Sciences. Due to the wide diversity of sport performance research, the remit of the Sport Performance section has been broad and includes mathematical and statistical evaluation of competitive sports performances, match- and notation-analysis, talent identification, training and selection or team organization. In addition, due to the academic interests of its section editors, they adopted a quality-assurance role for the Sport Performance section, invariably communicated through key editorials that subsequently shaped the editorial policy of the Journal. Key high-impact manuscripts are discussed, providing readers with some insight into what might lead an article to become a citation "classic". Finally, landmark articles in the areas of "science and football" and "notation analysis" are highlighted, providing further insight into how such articles have contributed to the development of sport performance research in general and the Journal of Sports Sciences in particular.